Complement C5a/C5aR pathway potentiates the pathogenesis of gastric cancer by down-regulating p21 expression - Chen, Jian; Li, Gui-qing; Zhang, Li; Tang, Ming; Cao, Xu; Xu, Gui-lian; Wu, Yu-Zhang (Cancer letters, 2018)
Although the complement C5a/C5aR pathway is suggested to play a critical role in tumor pathogenesis, the underlying mechanism has yet to be fully elucidated. In the present study, we found that in patients with gastric cancer in different clinical stages (from stageⅠto stage Ⅳ), both C5aR and p-PI3K/AKT levels were significantly higher in tumoral tissues than in adjacent non-tumoral tissues. In contrast, p21/p-p21 levels were significantly lower in tumoral tissues than in adjacent non-tumoral tissues. In vitro recombinant C5a administration remarkably promoted p-PI3K/p-AKT expression, but inhibited p21/p-p21 expression. Blockage of C5a/C5aR signaling with a C5aR antagonist reversed the C5a-induced inhibitory effect on p21/p-p21 expression. C5a administration to cells pre-treated with a PI3K inhibitor also prevented this inhibitory effect, suggesting the involvement of the PI3K/AKT signaling pathway in C5a/C5aR-mediated suppression of p21/p-p21 expression. In vivo C5aR antagonist treatment caused significant reduction in tumor growth in mice, accompanied by a remarkable elevation in p21/p-p21 expression and reduction in p-PI3K/AKT activation. These results indicate that the C5a/C5aR pathway promotes gastric cancer pathogenesis by suppressing p21/p-p21 expression via activation of PI3K/AKT signaling. •Complement C5a/C5aR pathway aggravates IR-induced acute kidney injury•C5a/C5aR pathway down-regulates PGRN expression after renal IR.•C5a/C5aR suppresses PGRN expression via the NF-kB-dependent manner.